(untitled) (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This article provides a comparative analysis of phraseological units expressing human character in English and Uzbek. The study examines the semantic, structural, and cultural features of phraseological expressions denoting positive and negative personality traits. The findings indicate that phraseological units serve as important linguistic tools reflecting a nation’s mentality, culture, and worldview. Although many English and Uzbek phraseological units share similar meanings, they differ significantly in their figurative representations and cultural origins.